2009
DOI: 10.1007/s11998-009-9175-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nanoadditives on surface, permeability and mechanical properties of self-organized organic–inorganic nanocomposite coatings

Abstract: Transparent and colorless nanocomposite coatings were prepared from a hybrid organicinorganic matrix and several inorganic nanofillers. The products are characterized by a high degree of self-assembling of the matrix which was prepared from an epoxy-functional organosilicon precursor and an oligomeric diamine. Unmodified and chemically modified montmorillonite, bentonite, laponite, and colloidal silica were used as nanofillers, differing in shape, size, and origin. The nanoadditive concentration in coatings wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In recent studies by the authors, [26][27][28] we have shown that the polymers D and T provide suitable matrices for the fabrication of low-loaded clay-containing nanocomposites. We found that very small amounts of layered silicates, e.g., 0.5 wt% provoke significant changes in mechanical properties and gas permeability.…”
Section: The Clay Nanofillers Testedmentioning
confidence: 97%
See 4 more Smart Citations
“…In recent studies by the authors, [26][27][28] we have shown that the polymers D and T provide suitable matrices for the fabrication of low-loaded clay-containing nanocomposites. We found that very small amounts of layered silicates, e.g., 0.5 wt% provoke significant changes in mechanical properties and gas permeability.…”
Section: The Clay Nanofillers Testedmentioning
confidence: 97%
“…We found that very small amounts of layered silicates, e.g., 0.5 wt% provoke significant changes in mechanical properties and gas permeability. 27 Scheme 3 shows the layered structure of the silicates of the montmorillonite type. Two thin silicate layers [Si 2 O 5 2À ] ¥ are connected mostly by magnesium cations and form a thicker rigid montmorillonite layer.…”
Section: The Clay Nanofillers Testedmentioning
confidence: 99%
See 3 more Smart Citations